Mammary analogue secretory carcinoma: an evaluation of its clinicopathological and genetic characteristics. Issue 7 (December 2015) - Luk, Peter P.; Selinger, Christina I.; Eviston, Timothy J.; Lum, Trina; Yu, Bing; O'Toole, Sandra A.; Clark, Jonathan R.; Gupta, Ruta
Abstract : Summary: Mammary analogue secretory carcinoma (MASC) is a recently described salivary gland malignancy. We evaluate the clinicopathological characteristics and long-term clinical behaviour of MASCs. A total of 190 primary salivary gland malignancies at a single institution were reviewed along with relevant immunohistochemical and fluorescent in situ hybridisation (FISH) studies to identify MASCs. Nine MASCs were identified predominantly in the parotid with an equal incidence in men and women and mean age of 36 years. The tumour size ranged from 14 to 50 mm (mean 22 mm). MASCs were composed of monotonous cells with vacuolated eosinophilic cytoplasm and a small nucleus with a distinctive nucleolus. All cases showed immunoreactivity with S-100, MUC4, CK7 and mammoglobin, and lacked immunoreactivity with DOG1, p63, CK5/6 and calponin. ETV6 rearrangement was seen in all cases. No mutations were identified using the OncoCarta Panel v1.0 Kit. Follow up was available for 0.4 to 22 years (median 4 years). Intraparotid lymph node involvement and local recurrence were seen in one patient each. There were no distant metastases. MASCs have specific histopathological features and immunohistochemical profile that distinguish them from their mimics. FISH plays a confirmatory role. An indolent long-term clinical course was observed in this cohort despite involvement of intraparotid lymph node and microscopically involved/close margins.